Kesetaraan Gender Di Tempat Kerja Serta Langkah-Langkah Untuk Memastikan Keadilan Dalam MSDM - Suci Cahyaningtyas Fatima; Ahmad Gunawan (CV. ITTC INDONESIA, 2023)
Discussing the issue of gender equality in human resource management (HR) in Indonesia. Gender equality is achieved when there is no discrimination between men and women, and both have equal access, the opportunity to participate, control development, and enjoy the same benefits and fairness in development. Although Indonesia has applied the principle of equality between men and women in front of the law, women are still far behind in various aspects that require special attention. Negative attitudes towards female workers, especially middle-class women, began to change after independence. But there is still a tendency to judge women based on their weaknesses. Women's participation in the labor force is increasing, which also contributes to Indonesia's development. The method used in this research is a qualitative descriptive method with the aim of clarifying and clarifying the subject matter of research, while gender analysis is a method or tool used to identify gender differences by analyzing data, facts, and information about gender.